Zarządzanie strategiczne w organizacjach non profit - Doniec, Alicja (Strategie management in a non-profit organization, 2006)
The article includes a wide characteristic of a non-profit organization, as well as the features that enable strategic management implementation. The author emphasizes the specific nature of the organization’s services and some of the forms of cooperation with public sector. The main advantages and disadvantages of the businesslike rules of the strategic management in a non profit organization are presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1137, s. 200-210